Pengaruh Digital Marketing, Harga dan Kualitas Produk Terhadap Kepuasan Pelanggan Pada Produk Es Teh Solo di Yogyakarta - Purnama Andri Murdapa; Anung Pramudyo (Sekolah Tinggi Ilmu Bisnis Kumala Nusa Yogyakarta, 2025)
The aim of this research is to examine the influence of digital marketing, price and product quality on customer satisfaction with Solo iced tea products in Yogyakarta. The respondents of this research were Solo iced tea customers in Yogyakarta. There were 100 people who were used as respondents in this research. The sampling technique used was convenience sampling. This research uses a questionnaire as a tool for data collection. The data analysis used in this research is multiple linear regression. The research results show that digital marketing, price and product quality influence customer satisfaction with Solo iced tea products in Yogyakarta. The advice that can be given is for Solo iced tea to maintain customer satisfaction by providing quality iced tea so that customers can last a long time and become loyal customers. Social media which is used as a promotional medium can also be used as a medium to build awareness. Can continue to build good price perceptions in front of customers and build a positive image through digital marketing, in this case social media.